2022
DOI: 10.2147/vmrr.s360669
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Associated Risk Factors of Mycoplasma gallisepticum Infection in Poultry Farms of Hawasa and Bishoftu, Central Ethiopia

Abstract: Background Mycoplasma gallisepticum (MG) infection is an economically important respiratory disease in the poultry production system worldwide. It is characterized by rapid transmission and causing many obstacles to poultry industries in different parts of Ethiopia. Methods A cross-sectional study was employed from January to September 2021 to estimate the seroprevalence and associated risk factors of MG in domestic layer chickens in large and small comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
4
1
Order By: Relevance
“…It is also the first report of widespread exposure to aMPV in the field, following initial detection in imported breeds at a government facility ( Hutton et al, 2017 ). The seroprevalence of IBV (94%) in the current study is similar to 97% seroprevalence in central Ethiopia reported by ( Shiferaw et al, 2022a ) but, the individual chicken seroprevalence of Mg in the scavenging production system (48%) is lower than the 76% seroprevalence reported by ( Shiferaw et al, 2022b ). ILTV was reported for the first time in the West and North Shewa zones of Ethiopia.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is also the first report of widespread exposure to aMPV in the field, following initial detection in imported breeds at a government facility ( Hutton et al, 2017 ). The seroprevalence of IBV (94%) in the current study is similar to 97% seroprevalence in central Ethiopia reported by ( Shiferaw et al, 2022a ) but, the individual chicken seroprevalence of Mg in the scavenging production system (48%) is lower than the 76% seroprevalence reported by ( Shiferaw et al, 2022b ). ILTV was reported for the first time in the West and North Shewa zones of Ethiopia.…”
Section: Discussionsupporting
confidence: 81%
“…The reported lower seroprevalence for ILTV in large intensive farms could be related to better biosecurity implementation in large-scale systems compared to the small-scale intensive production systems in the present study. The reported seroprevalence of Mg (46%) in intensive production system is lower than the report by ( Shiferaw et al, 2022b ) who reported 70.6% seroprevalence in Bishoftu and Hawassa towns of Ethiopia. Overall, chickens in the scavenging production system were seropositive for a greater number of respiratory pathogens than those in the intensive system.…”
Section: Discussioncontrasting
confidence: 70%
“…It is used to identify and quantitatively analyze molecules in biological samples by determining their presence and concentration (Coons et al, 1941). Shiferaw J et al (2022) conducted a study using the indirect ELISA method to detect the seropositivity of MG in commercially raised laying hens on poultry farms in Ethiopia. The overall serum positivity rate for MG infection was found to be 70.65%.…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%
“…However, the poultry industry faces challenges, including the risk of infections that can result in substantial economic losses. Mycoplasma gallisepticum (MG), a chronic respiratory disease that affects poultry, particularly layer birds, is the cause of avian mycoplasmosis (Ayim-Akonor et al, 2018;Shiferaw et al, 2022). MG infection leads to decreased egg production, carcass condemnation, and low mortality rates among layer birds.…”
Section: Introductionmentioning
confidence: 99%